Effect of Reoxidation on Inclusions Characteristic During Casting in Al‐Killed Steel Containing Rare Earth. Issue 10 (14th July 2022) - Wang, Yeguang; Liu, Chengjun
Abstract : To investigate the effect of reoxidation on inclusions characteristic during casting in Al‐killed steel containing rare earth, two industrial heats, including one of steady casting and the other of reoxidation, are performed with sampling from Rheinstahl Heratus, tundish, submerged entry nozzle, and slab. In the present study, air absorption occurs at the submerged entry nozzle and caused the reoxidation of molten steel. As a result, the number of inclusions increases significantly, and nearly spherical Ce2 O2 S inclusions are transformed to clustered‐like CeAlO3, which increases the average size of inclusions from 3.92 to 9.21 μm, thereby resulting in serious nozzle clogging and slab defects. The results of thermodynamic calculation show that Ce2 O2 S is transformed to CeAlO3 with total oxygen content increases under different Ce additions, and this transformation of inclusions can be inhibited by controlling the value of [Ce]/[O] above 2.12. Based on the experimental results and the theoretical analysis, the evolution mechanism of inclusions during reoxidation is clarified. This study can provide theoretical guidance to alleviate the harm of reoxidation to Al‐killed RE‐steel from the inclusion‐controlling perspective. Abstract : The effect of reoxidation on inclusions characteristic is investigated through industrial experiments. The dispersed nearly spherical Ce2 O2 S inclusions are transformed to large‐sized CeAlO3 clusters during reoxidation, thereby causing nozzle clogging and slab defects. The mechanism and control condition of rare earth inclusions evolution during reoxidation are revealed by using thermodynamic calculation.